Ultraviolet Lights Effect on Farmer Health and Productivity: Literature Review - Enggal Hadi Kurniyawan; Angela Irena Junanda; Hersanti Maulia Putri H; Meri Katrin Dwi Cayani; Alfid Tri Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur (KHD-Production, 2023)
Cumulative exposure to solar UV radiation is linked to chronic skin and eye diseases such as skin cancer, photoaging, actinic keratosis, pterygium, cataracts, and possibly macular degeneration. This study aims to determine farmers' knowledge about UV rays on eye health in anticipating the dangers of excessive UV rays and increase farmer awareness of the sources and risks of UV rays for eye health. The method used is a literature review to examine the effects of UV Lights on the health and productivity of farmers in more depth. This literature search was conducted until March 19, 2023, using the PubMed and Science Direct article search engines, with the following search terms using the BOOLEAN Operator technique: